A novel function and mechanism of ischemia-induced retinal astrocyte-derived exosomes for RGC apoptosis of ischemic retinopathy - Xiaoyuan Ye; Yunfei Liu; Congying Chen; Yimeng Sun; Fan Li; Yunzhao Fu; Jiawen Luo; Lishi Su; Wei Chi (Molecular Therapy: Nucleic Acids, 2024)
Retinal ischemia is a common clinical event leading to retinal ganglion cell (RGC) death, resulting in irreversible vision loss. In the retina, glia-neuron communication is crucial for multiple functions and homeostasis. Extracellular vesicles, notably exosomes, play a critical role. The functions and mechanisms of retinal astrocyte-secreted exosomes remain unclear. Here, we isolated astrocyte-derived exosomes under hypoxia or normoxia and explored their role in an in vivo retinal ischemia-reperfusion (RIR) model. We found that hypoxia triggered astrocytes to produce a significantly increased number of exosomes, which could be internalized by RGCs in vivo or in vitro. Also, in the RIR model, the hypoxia-induced exosomes ameliorated the RIR injury and suppressed the RGC apoptosis. Furthermore, microRNA sequencing of retinal astrocyte-secreted exosomes revealed different patterns of exosomal miRNAs under hypoxia, particularly enriched with miR-329-5p. We verified that miR-329-5p was specifically bound to mitogen-activated protein kinase 8 mRNA, and subsequent JNK-pathway molecules were downregulated. We anticipated that the miR-329-5p/JNK pathway is a key to suppressing RGC apoptosis and preventing RIR injury. Such findings provided insights into the therapeutic potential of hypoxia-induced astrocyte-secreted exosomes and the miR-329-5p for treating retina ischemic diseases.